Robust parameter design of shielded metal arc welding (smaw) for optimum tensile strength. (December 2020) - Setiawan, M.D.I.; Pradana, Y.R.A.; Suprayitno,
Abstract: Shielded Metal Arc Welding (SMAW), an arc welding process that uses a consumable electrode consisting of a filler metal rod coated with chemicals that provide flux and shielding, is widely used in engineering applications. SMAW parameters that usually applied in practice is still possible to be optimized to improve the process to become robust. This work is focus on an optimization of SMAW process on ASTM A500 Hollow Square Pipe, as it is widely found in applications. The welding parameters such as welding current, electrode angle, root gap, and electrode type are adopted as process parameters. Taguchi robust optimization is applied as optimization strategy, and L9 fractional orthogonal array is selected as design of experiment. The optimization objective is to maximize tensile strength of SMAW welded joint. The optimization results found that welding current 100A, electrode angle 90o, root gap 2 mm, and electrode type E7018 of SMAW parameters give the optimum tensile strength. The tensile strength gain of robust design based on the initial design was carried out by 98, 39 MPa (from 259, 45 MPa of initial design to 357, 84 MPa of optimum design).